Coronavirus Disease 2019 in Pediatric Emergency Room: The Dilemma of Cycle Threshold Value - Timur, Demet; Demirpek, Ugur; Demirbaş, Başak Ceylan; Türe, Esra; Korkmaz, Muhammed Furkan; Timur, Ahmet (Journal of Pediatric Infectious Diseases, 2022)
Objective The havoc caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic could not have been predicted, with children being affected worldwide. Testing for SARS-CoV-2 infection helped to define the interventions against the spread of the disease. A polymerase chain reaction (PCR) test has been the mainstay of diagnostic testing. Cycle threshold (Ct) is a semiquantitative value that indicates approximately how much viral genetic material was in the sample. The aim of this study was to evaluate the impact of Ct values among children with SARS-CoV-2 infection.Methods Between May 3, 2020 and August 3, 2020, clinical laboratory input and the data of patients with positive SARS-CoV-2 PCR tests were retrospectively studied.Results There was no statistical significance between Ct values and the patient's status, symptoms other than fever, or other laboratory findings. However, the Ct value of patients who had symptoms at the time of admission to the hospital was significantly lower.Conclusion In this study, symptomatic patients had lower Ct than asymptomatic patients that reflected higher viral loads. In evidence-based medicine applications, it might be useful to correlate the clinical history with laboratory test results. Even symptomatic patients with high Ct value coinfections, or an alternative acute infection, should be considered.
Keywords: Children; COVID-19; Cycle Threshold; RT-PCR; pandemic